Manifestações patológicas em edificações recentes: causas e consequências - Lopes, Sanderson Aires (Universidade Federal Rural do Semi-Árido, 2020)
Pathological manifestations are a fact that has affected buildings of the most varied types and in the most varied locations, with consequences ranging from an unforeseen expense to a complete interdiction, in this way the present paper seeks to investigate constructions in a northeastern municipality, with the objective of finding and analyzing pathological evidence that affects civil engineering projects, including recent constructions, in addition to inferring about its main causes, discussing the consequences that they bring for the structures in question and suggest viable and effective solutions for each pathology found and specific situation. For that, definitions are raised about the pathologies according to authors of the area in the theoretical framework, aiming to present the possible causes and discuss about each pathology itself. Then, a descriptive-qualitative case study is performed in which photographic records of buildings affected by various pathologies were made and the possible causes and solutions for them.
Artigo
Keywords: Construção civil; Patologias; Recuperação; Civil construction; Pathologies; Recovery; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA